A Modern Technique for Evaluating the Square Root of a Complex Number (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
The subject of complex numbers issue is very significant because of its wide utility, especially in the engineering circuits representation.  In this paper, a modern method to find the square root of the complex number has been analyzed, and some examples on the subject were presented.